Children's plays for creative actors; a collection of royalty-free plays for boys and girls. - Boiko, Claire; Boiko, Claire (Plays, inc., 1971)
Thirty-five one-act plays, most with fifteen or twenty minutes playing time, including fantasies, comedies, and several appropriate for different holidays. Includes production notes.